PALYNOLOGICAL STUDY OF PALEOZOIC SEDIMENTS OF THE CHAL-I-SHEH AREA, SOUTHWESTERN IRAN (Journal of Sciences, Islamic Republic of Iran)
The Paleozoic sediments of the Chal-i-Sheh area in southwestern Iran comprising of Mila Formation, Ilebek Formation and Faraghan Formation, were studied palynologically. The samples containing well-preserved palynomorphs include acritarchs, chitinozoans, scolecodonts and pollenlspores. A palynological zonation has been established and comparison was made with other parts of the world. Based on stratigraphic potential of the diagnostic taxa, the Mila Formation is uppermost Cambrian to lowermost Tremadocian, Ilebek'Formation Tremadocian and the Faraghan Formation is Lower Permian. Therefore, there is a hiatus within the Paleozoic sequence of the Chal-i-Sheh area extending from Upper Ordovician into the Lower Permian. This hiatus possibly coincides with Hercynian Orogeny which resulted in the emergence of the Zagros Basin and produced extensive erosion. Comparing palynomorphs of the Paleozoic sediments of Chal-i-Sheh with published palynological data, reveals that the Zagros Basin has been part of the "Mediterranean Acritarch Province" during the Lower Ordovician. The presence of gondwanic palynomorphs within the Faraghan Formation suggests a gondwanic relationship in the Permian period.